Analisis Kesulitan Belajar dalam Pembelajaran Membaca Cepat Siswa Kelas V Sekolah Dasar Beserta Solusi yang Ditawarkan Menggunakan Metodequantum Reading - Julinda Julinda; Laura Viorenza; Pilsa Marsinta (Universitas Palangka Raya, 2024)
Efforts must always be made to improve students' reading abilities in elementary school students, especially as reading, which is part of literacy, is very poor, especially for elementary school students. The quantum reading method is an ideal method to be implemented in elementary schools so that students can continue to increase their interest in reading. The research aims to examine the application of the quantum reading method in elementary schools, both in essence and in theoretical-based applications.This research is based on facts in the field, namely students' low interest in reading, no initiative to read books, lack of reading activities, and unsupportive library facilities. So students often experience difficulties in learning to read, especially in speed reading. So the author took the initiative to describe the analysis of learning difficulties in learning to read quickly for fifth grade elementary school students along with the solutions offered using the quantum reading method.The formulation of the problem in this research is how to increase students' reading interest who use the quantum Reading method and conventional reading methods in Indonesian language subjects in Grade V Elementary Schools. This research aims to determine the increase in reading interest of students who use the quantum reading method and conventional methods in schools. Base.